Biological aspects of Lema quadrivittata (Coleoptera: Chrysomelidae), leafminer of Commelina erecta in Argentina - DEFAGÓ, MARÍA TERESA; FENOGLIO, MARÍA SILVINA; SALVO, ADRIANA (Revista Colombiana de Entomología, 2010)
Biological aspects of Lema (Neolema) quadrivittata, leafminer of Commelina erecta, were studied, and for the first time two genera of parasitoids associated with the leafminer are reported.